Banking Secrecy in Malaysia - Cheong, May Fong (Journal of Malaysian and Comparative Law, 2019)
The duty of confidentiality of secrecy owed by a bank towards its customer is a vital aspect of the banker and customer relationship. This is a contractual duty implied by the common law and the leading case is Tournier v National Provincial and Union Bank of England. Besides the contractual duty, a bank is also under a statutory duty of secrecy imposed by the Banking and Financial Institutions Act 1989 (hereinafter referred to as the "BAFIA").